Analysis of twitter user sentiment on the monkeypox virus issue using the nrc lexicon - Muhammad Khahfi Zuhanda; Anil Hakim Syofra Syofra; Devy Mathelinea; Prana Ugiana Gio; Yuan Anisa Anisa; Nanda Novita (Jurnal Mantik, 2023)
Monkeypox virus is closely related to variola (smallpox virus) and causes a smallpox-like disease. The increase in monkeypox cases has caused the general public to be involved in providing responses to seek and share information related to monkeypox on the internet, especially on social media platforms. This study aims to analyze a collection of 5000 tweets on August 5, 2022, for sentiment analysis using the NRC lexicon. Of the 5,000 tweets that have been extracted, it is obtained that the words that Twitter users often use are "health", "emergency", "public", "covid", and "declares". By using the classification using the NRC lexicon comparison, we found that the emotion type of fear was the most widely used emotion, which had a presentation of 19.73%, followed by anticipation emotion at 16.78%, sadness 14.77%, trust at 13.90%, anger 9.99%, shock 9.14%, disgust 8.12%, and happy 1288 7.90 %. The negative sentiment that often appears on Twitter is equal to 51.92%, and positive sentiment has a percentage of 48.08%. The negative sentiment words that appear most often are "emergency", "virus", "disease", "shit", and "risk". The positive sentiment words that appear most often are "public", "vaccine", "sex", "contact", and "united". The analytical method with the lexicon method is very well used in analyzing various emotions and sentiments on social media. %MCEPASTEBIN%